Management of Gastrointestinal Symptoms in Parkinson’s Disease - Han-Lin Chiang; Chin-Hsien Lin (Journal of Central Nervous System Disease)
Gastrointestinal (GI) dysfunction is a common and often underappreciated aspect of Parkinson’s disease (PD), with symptoms manifesting at multiple levels of the digestive tract, from swallowing difficulties to challenges with defecation. These non-motor symptoms can be more debilitating than the hallmark motor impairments of PD, profoundly affecting patients’ quality of life. The burden of GI issues in PD extends beyond discomfort, contributing to malnutrition, weight loss, and impaired medication absorption, which can exacerbate both motor and non-motor symptoms. Despite their clinical significance, GI symptoms are frequently overlooked or mismanaged in routine practice. Inappropriate treatments, including certain medications and dietary recommendations, may inadvertently worsen the disease course. Therefore, a comprehensive understanding of GI dysfunction in PD is critical for clinicians, especially neurologists, to optimize patient care. This review provides an updated overview of the common GI manifestations in PD, including drooling, dyspepsia and dysphagia, gastroparesis, constipation, H. pylori infection, and small intestinal bacterial overgrowth. We discuss current diagnostic approaches, non-pharmacological and pharmacological treatment strategies. Recognizing and appropriately managing GI dysfunction in PD is essential for optimizing symptom control and improving patients’ overall well-being.